A new species of betel nut palm (Areca: Arecaceae) from western New Guinea - Heatubun, Charlie Danny; Iwanggin, Marthinus P.; Simbiak, Victor I. (Phytotaxa, 2013)
A new species of betel nut palm, Areca unipa, is described and illustrated here for the first time. This is the second species of Areca from New Guinea that is closely related to the widespread, cultivated species A. catechu. A discussion of its morphological characters, distribution, ecology, habitat, uses and conservation status is provided.